PENGARUH PENDAPATAN, INVESTASI, DAN PRILAKU KEUANGAN TERHADAP TINGKAT LITERASI KEUANGAN UKM KOTA PALEMBANG - Putra, Dimas Pratama (Institut Rahmaniyah Sekayu, 2024)
Financial literacy is something important that has a big impact on individuals, families and the economy as a whole. Additionally, a good understanding of finance helps individuals and households, as well as companies, including SMEs, make better financial decisions. factors that influence financial literacy, namely: education level, income level, financial behavior and investment, therefore further research is needed to determine the results achieved. The aim of this research is to study how income, investment and financial behavior influence the financial literacy of small and medium SMEs in Palembang City. Research Objects in Palembang City UKM. Quantitative descriptive method using primary data sources. Determining the sample uses the Slovin formula by distributing questionnaires using random sampling. The results of the analysis show that the financial literacy of SMEs in Palembang City is influenced simultaneously and partially. Based on these results, there are findings that the higher the level of financial literacy a person tends to be, the wiser they will be in managing their income, investments and financial behavior.